PENENTUAN BOBOT PORTOFOLIO OPTIMAL DENGAN METODE RESAMPLED EFFICIENT FRONTIER UNTUK PERHITUNGAN VALUE AT RISK PADA DATA BERDISTRIBUSI NORMAL - Esti Pratiwi; Abdul Hoyyi; Sugito Sugito (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
The investors have a goal of getting return when they invest their wealth, but on the other hand they should bear the risk that might arise from their investment. There are three categories of investors based on their preferences toward risk that is risk averter, moderate risk and risk taker. To establish a portfolio that is able to incorporate investor preferences is used Resampled Efficient Frontier Method. Resampled Efficient Frontier Method is a development of the Mean Variance Efficient Portfolios Method, which used Monte Carlo simulation to obtain more estimated of parameter inputs. Based on the efficient portfolios of Resampled Efficient Frontier along the efficient frontier with 51 efficient points, taken optimal portfolio for each investor type. Optimal portfolio for risk averter, moderate risk and risk taker respectively is an efficient portfolio on the first point, 26th point, and 51st point. To describe the loss of the optimal portfolio is used Value at Risk. VaR is calculated based on monthly return from BBCA, LPKR, PGAS and SMGR during January 2008 until December 2013. Estimated VaR on 95% confidence level during 20 days holding period and the amount of investment allocation Rp 100,000,000.00 from the optimal portfolio for risk averter, moderate risk and risk taker respectively is Rp 50,706,000.00, Rp 54,618,000.00 and Rp 64,522,000.00